2003
DOI: 10.1186/bcr609
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer in association with thyroid disorders

Abstract: AITD = autoimmune thyroid disease; ER = oestrogen receptor; FNA = fine-needle aspiration; T 3 = triiodothyronine; T 4 = thyroxine; TSH = thyroidstimulating hormone; TPO = thyroid peroxidase. Breast Cancer ResearchVol 5 No 5 Turken et al. Research article Breast cancer in association with thyroid disorders Methods:Clinical and ultrasound evaluation of thyroid gland, determination of serum thyroid hormone and antibody levels, and fine-needle aspiration of thyroid gland were performed in 150 breast cancer patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
128
0
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(152 citation statements)
references
References 27 publications
7
128
0
4
Order By: Relevance
“…However, the relationship between breast cancer and thyroid hormone is controversial. Even though many studies have shown that thyroid diseases are common in women with breast cancer, other reports have not confirmed this association (reviewed in 7,8). Almost every form of thyroid disease including hyperthyroidism has been identified in association with breast cancer (9-11).…”
Section: Introductionmentioning
confidence: 97%
“…However, the relationship between breast cancer and thyroid hormone is controversial. Even though many studies have shown that thyroid diseases are common in women with breast cancer, other reports have not confirmed this association (reviewed in 7,8). Almost every form of thyroid disease including hyperthyroidism has been identified in association with breast cancer (9-11).…”
Section: Introductionmentioning
confidence: 97%
“…Other factors, such as genetic mutations, environmental agents and immunomodulatory treatments, can also play roles (6). There are few authors who have directly indicated the increased risk of breast cancer in patients with autoimmune hypothyroidism and multiple sclerosis (18,19). Interestingly this case can be another example to study more about these associations.…”
Section: Discussionmentioning
confidence: 99%
“…Full--text ar+cles assessed for eligibility (n =21) Figure.1) (Turken et al, 2003;Cengiz et al, 2004;Kuijpens et al, 2005;Saraiva et al, 2005;Giustarini et al, 2006;Ditsch et al, 2010;Ali et al, 2011;Szychta et al, 2013) . Tables 1 and 2 show the characteristics and data of all 8 studies included in our analysis.…”
Section: Iden0fica0onmentioning
confidence: 99%
“…Thyroid diseases (TD) are frequently encountered in clinical practice and are more common among women (Vanderpump 2011). Breast cancer (BC) is a hormone-dependent neoplasm (Turken et al, 2003;Uyeturk et al, 2013). Various thyroid disorders have been detected in breast cancer patients (Smyth et al, 1996;Kuijpens et al, 2005;Ditsch et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation